2011
DOI: 10.1097/aln.0b013e31821950c2
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Spinal Substance P Release by Intrathecal Calcium Channel Blockade

Abstract: Background We investigated the role of different voltage sensitive calcium channels expressed at presynaptic afferent terminals in substance P release and on nociceptive behavior evoked by intraplantar formalin by examining the effects of intrathecally delivered N- (ziconotide), T- (mibefradil) and L-type voltage sensitive calcium channels blockers (diltiazem and verapamil). Methods Rats received intrathecal pretreatment with saline or doses of morphine, ziconotide, mibefradil, diltiazem or verapamil. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 61 publications
2
35
1
Order By: Relevance
“…The effect of ω-conotoxin GVIA on after-discharges was similar to that of morphine and a neurokinin 1-receptor antagonist, respectively, administered intravenously (25). These results are supported by studies indicating that N-type VDCCs were inhibited by μ-opioid receptors in the DRG (35,36) and that N-type VDCC blockers inhibited the release of substance P in the spinal cord (8,37,38).…”
Section: Figsupporting
confidence: 75%
“…The effect of ω-conotoxin GVIA on after-discharges was similar to that of morphine and a neurokinin 1-receptor antagonist, respectively, administered intravenously (25). These results are supported by studies indicating that N-type VDCCs were inhibited by μ-opioid receptors in the DRG (35,36) and that N-type VDCC blockers inhibited the release of substance P in the spinal cord (8,37,38).…”
Section: Figsupporting
confidence: 75%
“…In present study, we did not analyze the pain behavior after SP injection, and there was no behavioral change or extraordinary reaction after injection compared with the control group. However, many studies suggested that SP of the spinal cord is linked closely to nociceptive change [40][41][42]; so, a welldesigned study is needed to clarify the pain behavior after SP injection.…”
Section: Discussionmentioning
confidence: 99%
“…Later clinical studies established that SNX-111 effectively reduced the pain associated with cancer or AIDS (Staats et al, 2004). More recently, intrathecal administration of SNX-111, but not the L-type blockers diltiazem or verapamil, suppressed the internalization of neurokinin-1, the G-protein coupled receptor that is activated by substance P (Takasusuki and Yaksh 2011). These results demonstrate that N-type Ca 2+ channels play a key role in the transmission of nociceptive signaling in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%